Value of Nontechnical Skills in Minimally Invasive Surgery - Araujo, Sergio Eduardo Alonso; Kim, Nam Jin; Cendoroglo, Neto Miguel; Klajner, Sidney (Clinics in Colon and Rectal Surgery, 2021)
Nontechnical skills are of increasing importance in surgery and surgical training. The main studies on its impact on the safety and effectiveness of surgical interventions were mainly published in the first decade of the 2000s. Due to the significant technical complexity and great diversity of instruments for nontechnical skills evaluation, the interest in training and in measuring the impact on surgical safety has relatively decreased. However, the advent of minimally invasive surgery and its peculiar technical characteristics of sophisticated technique and constant innovation through the adoption of new materials and drugs has rekindled interest in this expertise area.In the present review, we have revisited the main instruments available to measure nontechnical skill of surgical teams and analyzed the role of the main competencies on which they are based, such as situational awareness, leadership and communication skills, and the consistency of the intraoperative decision-making process.We conclude that despite the great consensus that exists among all members of the health team on the importance of nontechnical skills for the surgical team in minimally invasive surgery, the reproducible evidence on the subject is scarce and laborious to obtain. To the extent that protecting and expanding nontechnical skills is fundamental to the path toward the high reliability of health institutions, it is possible to anticipate here the role of these institutions as promoters of continuity and new research models in this area of knowledge, especially in minimally invasive surgery, an access route to which more and more patients undergoing surgical treatment in these same institutions are submitted.
Keywords: nontechnical skills; minimally invasive surgery; surgical training